Papillary breast cancer: A retrospective single‐centre clinical study. Issue 5 (24th January 2020) - Layton, Thomas B.; Phillips, Benjamin; Remoundos, Dionysios D.
Abstract: Papillary carcinoma (PC) of the breast is a rare malignancy that accounts for 0.5%‐1% of breast cancers. PC remains an understudied cancer, and we still require further information on its behaviour, staging and management. In particular, a significant proportion of PC cases still undergo sentinel lymph node biopsy without clear empirical justification. In the present study, we provide a valuable cohort of 44 PC patients and examine the clinicopathological features and outcome of loco‐regional staging. Our results provide important insights into the behaviour of PC and suggest SLNB may be spared in this condition. Crucially, we show only one histologically confirmed PC case had evidence of nodal metastasis. In addition, up to 5 years postsurgery, no patient in our cohort died from their cancer. Together, our results support further work in the utility of SLNB in PC and highlight the favourable prognosis of this tumour. We propose SLNB should not be routinely indicated for patients with PC treated with breast conservation, and future studies should aim to incorporate prospective data to help inform optimal management of PC.